(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Mountain communities have unique issues, being generally geographically remote, and politically and socially neglected. The objective was to evaluate the health and healthcare access of children in Tissar, a mountain village in Gilgit-Baltistan. Subjects and methods: This was a cross-sectional study conducted in August 2021, in Tissar, Gilgit-Baltistan (GB), in Northern Pakistan. Interviews were conducted of adults over the age of 18 years, who had at least one child of age12 years and below, using a convenience sampling method. Descriptive summary statistics were computed using statistical software R version 4.1.2. Poisson regression was used to find potential risk factors associated with diarrhea and pneumonia. Results: Semi-structured interviews were conducted on 400 participants. Although 363 (90.8%) people grew their own food; 203 (50.7%) still needed to purchase food with only 213 (53.2%) receiving up to three meals a day. Access to healthcare was perceived as inadequate, with only 42 (10.5%) satisfied with the healthcare their children were receiving. Up to 268 (67%) needed to borrow money or could not afford healthcare. Annual occurrence of diarrhea and pneumonia was reported in 100% households, most reporting repeated episodes in one year per child. On Poisson Regression, number of meals per day was negatively associated with diarrhea (rate ratio=0.646, 95%CI=0.591-0.706, p<0.001), adjusted for weaning. Number of meals per day was also negatively associated with pneumonia (rate ratio 0.529, 95%CI=0.487-0.574, p<0.001), adjusting for education and number of children in the family (>6 versus <6). Conclusion: Health of Children needs to be addressed in mountain communities in Pakistan.